Supply chain performance in the age of Industry 4.0 - Tahsina Khan; Md Mehedi Hasan Emon (Brazilian Journal of Operations & Production Management)
Goal: This study investigates the impact of Industry 4.0 adoption on supply chain performance in Bangladesh’s manufacturing sector, emphasizing the mediating roles of digital supply chain integration, supply chain innovation, and supply chain visibility.